Recovery and characterization of Lucuma seed starch (Pouteria lucuma) with potential industrial application [Recuperación y caracterización del almidón de semilla de Lúcuma (Pouteria lucuma) con potencial aplicación industrial] - Alvarez-Yanamango E. (2020)
Today starches have multiple industrial applications and have gained value as the raw material for the production of biodegradable packaging. Despite having been extracted from innumerable plant sources such as potatoes, corn, cassava, wheat, rice, quinoa, banana, etc,. The search for new low-cost sources continues to be important, seeking not to limit access to these traditional sources, which are the basis of alimentation in developing countries. For this reason, the objective of this research was to take advantage of the lucuma seed as a source for the isolation of starch, whose physicochemical and functional characterization would allow us to know its performance and its potential industrial application. For the isolation of the native starch, a sequence of physical operations using pilot equipment will be used, while the characterization tests included by physicochemical tests (% total starch, % humidity, % ash, water activity, % acidity, and pH) and functional properties: solubility index (ISA), swelling power (HP), water absorption capacity (CAA) and clarity of the paste. The results found that the total starch present in the lucuma seed is 83.97%. The functional properties show an ISA (15.55%), CAA (23.61 g of water / g of starch), HP (27.98 g of water / g of starch), and clarity of the paste of 18.67%, demonstrating the potential for possible uses in various industrial food processes. © 2020 Latin American and Caribbean Consortium of Engineering Institutions. All rights reserved.